Design and Construction of an Automatic Egg Incubator Based on the Atmega 328 Microcontroller - Hannan Asrawi; Iskandar Zulkarnaini; Septiannur Septiannur (Universitas Malikussaleh, 2026)
An ATmega328 microcontroller is used as the control center connected to the DHT11 sensor in the automatic egg incubator. The LCD is used to display and monitor temperature and humidity values ​​in real time. Temperature and humidity are two main factors that greatly influence the success of the egg hatching process, in addition to air circulation and egg rotation. However, simple egg incubators on the market generally only focus on temperature and humidity control displayed on the LCD. System testing was carried out using an experimental method, namely through direct trials using the designed egg incubator. Several eggs were placed in the machine to be conditioned according to the specified parameters. Temperature and humidity monitoring was carried out via the LCD for the first two hours with a check interval of every 10 minutes. The system is also equipped with an automatic egg rotation mechanism using a 5-volt servo motor. The servo functions to move the egg rack to produce an 18° tilt angle alternately and continuously, to ensure even heat distribution. The DHT11 sensor is capable of detecting temperature and humidity levels suitable for the incubation process of chicken eggs, which range from 36°C to 39°C and humidity levels between 55% and 65%. This study aims to implement a temperature and humidity control system in a chicken egg incubator to increase the percentage of successful hatching and ensure the servo motor can work properly in automatically adjusting the position of the egg rack according to the specified time.